Year-to-year variation in organic fertilization effects on soil carbon stabilization and microbial networks - Ma, Mingkun; Yang, Hao; Yang, Jigang; Chen, Shanghong; Lei, Fang; Liu, Dinghui; Yang, Zepeng; Chen, Honglin (Frontiers in Microbiology, 2025)
ObjectiveSoil organic carbon (SOC) stabilization is a key process linking soil fertility and climate change mitigation; however, its microbial regulatory mechanisms under organic fertilization remain unclear. This study aimed to elucidate how different rates and combinations of organic fertilization regulate SOC fractions, enzyme activities, and microbial communities in newly reclaimed farmland.MethodsA two-year field experiment (2024–2025) was conducted under a maize–oilseed rape rotation system in Sichuan, China. Treatments included conventional fertilization, varying rates of organic fertilization, and combined organic–inorganic fertilization. SOC fractions, enzyme activities, and microbial community composition were analyzed, and structural equation modeling was applied to explore the microbial and enzymatic pathways driving SOC stabilization.ResultsOrganic fertilization enhanced both labile and stable carbon pools. Readily oxidizable carbon (ROC) and dissolved organic carbon (DOC) increased under moderate inputs, while mineral-associated organic carbon (MAOC) accumulated under higher inputs. Enzyme activities mirrored these changes, with laccase activity enhanced under high organic inputs and cellobiohydrolase suppressed by sole organics but restored under combined fertilization. Microbial analysis showed enrichment of Proteobacteria, increased diversity, and year-specific shifts in Actinobacteriota. Moderate labile carbon inputs promoted stable carbon formation in the first year, whereas excessive inputs in the second year reduced microbial efficiency, increased network complexity, and weakened stabilization.ConclusionModerate organic fertilization improved rapeseed yield and carbon sequestration efficiency by promoting stable carbon accumulation, oxidative enzyme activity, and functional microbial diversity. These findings reveal the microbial and enzymatic mechanisms underlying SOC stabilization in newly reclaimed farmland and provide practical guidance for balanced fertilization strategies to enhance carbon storage while sustaining crop productivity.